Squamous cell carcinoma of buccal mucosa: Prevalence of clinicopathological pattern and its implications for treatment - Ramasamy Padma; Sathish Paulraj; Sivapatham Sundaresan (Wolters Kluwer Medknow Publications, 2017)
Background: In developing countries, oral squamous cell carcinoma is a leading cause of mortality due to late diagnosis. Hence, the aim of the study was to analyze the clinical and pathological presentation of buccal mucosa carcinoma patients. Materials and Methods: A case series study was conducted in regional cancer centre, Tamil Nadu. Demographic and clinical details were collected from medical registries between 2013 and 2015. Results: The present study consists of 198 cases which comprised 125 (63.1%) male and 73 (36.9%) female. The mean age of the cases was 54.16 ± 17.25 years. Histopathology reports showed most frequency of well-differentiated buccal squamous cell carcinoma 98 (49.5%) and followed moderate 98 (34.3%) and poorly differentiated 32 (16.2%). Clinical tumor nodal metastasis reports revealed 168 (85%) of advanced clinical stage (III and IV) of buccal mucosa carcinoma, whereas only 30 (15%) was presented at early stage (I and II) of disease. Based on the clinical and histopathological analysis, 86 (43.4%) cases were fit for surgery and followed by adjuvant chemo- - and radio-therapy. Of 198 cases, the most common clinical complaints were identified with 73 (38%) pain and followed by 47 (28%) bleeding, may be due to unawareness or ignorance of disease. Conclusion: The study concluded that most of the cases had diagnosed in advanced stage of tumor with severe pain and bleeding. Hence, further studies warrant on awareness of clinical symptoms and also to analyze the risk factors for delay diagnosis in Tamil Nadu population, which might reduce morbidity and mortality.